posted by .

I need help with solving this equation
and the steps on how to do it?

  • Math -

    well for this question the whole goal is to get all the x's on one side and all the numbers on the other side.

    1st combine all like terms on the same sides


    -11x-28 = 17x-14

    then go and bring the x's over to one side and the numbers over to the other side(subtract or add)

    -28x= 14

    then divide to get x

    x= 14/(-28)

    so what do you get?

  • Math -

    Add like terms. For example, on the left
    5X + 22X - 38X = -11X
    on the right -17 -9 + 12 = -14
    -11X-9-19 = 17X-14
    Combine the -9 and -19
    Now add 28 to both sides
    -11X-28+28 = 17X-14+28
    Subtract 17X from both sides
    Multiply both sides by -1
    28X = -14
    Divide both sides by 28
    X = -1/2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    solve the equation 20x^3 +44x^2 -17x -5 given that -5/2 is a zero of f(x) 20x^3 +44x^2 -17x -5 I used synthetic division and got 20x^2-6x-2=0 took 2 and divided it out of that equation 2(x+5/2)=10x^2 -3x-1 then i factored it out the …
  2. math

    17x – 42 = -39 i need to show the steps for solving this equation
  3. Algebra, help

    So, I've written down 22x+70=17x-95 and I think you would add together 22 and 17, to get 39x right?
  4. Ciollege algebra

    Suppose that X liters of 38% acid solution are mixed with y liters of a 42% solution to obtain 100L of a 39% solution. One equation in a system for solving this problem is x+y=100. Which one of the following is the other equation?
  5. math

    solving equation 20x-7=2+17x
  6. math

    determine between which consecutive integers the real zeros of each function are located. f(x)=3x^3 – 10x^2 + 22x – 4 (I got 0,1) f(x) = x^3 – 12x^2 + 17x – 9 (NO idea) f(x) = x^3 – 9 (I got 8,9) Thanks for the help, I really …
  7. Algebra 1

  8. pre-Algebra

  9. calculus

    find the derivative of y y= 2 (22x+31)^(3/2)+ arctan((22x+21)^(1/2))+ln(11x+16)-22x-30
  10. Math help Steve?

    1) Given that p(-3), p(-1), and p(5)=0, which expression could be p(x)?

More Similar Questions